Loneliness and social networks of older adults in rural communities: a narrative synthesis systematic review - Hussain, Basharat; Mirza, Mahrukh; Baines, Rebecca; Burns, Lorna; Stevens, Sebastian; Asthana, Sheena; Chatterjee, Arunangsu (Frontiers in Public Health, 2023)
Introduction Loneliness has significant impacts on the health of older adults. Social networks help to improve psychosocial and quality of life outcomes among older adults. A fifth of older adults live in rural communities, where geographic isolation poses challenges to health. The dynamics of social networks of older adults in rural communities has not been explored. Objective To synthesize the literature related to loneliness and social networks of older adults in rural settings. Methods A mixed-methods systematic review was conducted through searching six bibliographic databases to retrieve peer-reviewed literature with no time limits. We performed a methodological assessment of each study using a mixed method quality assessment tool. Findings are synthesized thematically. Results A total of 50 studies (32 quantitative, 15 qualitative, and 3 mixed methods) were included in this review. Studies were conducted in 17 different countries, the majority from China (n = 12), the UK (n = 9), and USA (n = 9). Findings revealed that social networks of older adults consist of family, friends and neighbors and continue to be developed through participation in various physical and social activities such as walking groups and participation in religious events. Social networks offer informational, functional, psychological and social support to older adults. Through their social networks, older adults feel socially connected and cared for. Successful interventions to improve social networks and address loneliness were those developed in groups or one-on-one with the older adults. The key ingredient to the positive impact of these interventions on reducing social isolation and loneliness was the formation of a social connection and regular engagement with the older adults. However, the review did not find any explicitly reported theory or model on which these interventions are based. Conclusion The prevalence of loneliness among older adults in rural areas needs urgent attention. Social network theory and methods can help in developing interventions to address social isolation and loneliness among older adults in rural communities.